The SAWASDEE by AOT Application is Relevant to Modern Marketing Strategies 4Es and Service Quality of Suvarnabhumi Airport - เรืองอริยภักดิ์ ดร.เนตร์ศิริ (KBU Journal of Aviation Management:KBUJAM, 2023)
Objectives: 1) to survey personal data of SAWASDEE by AOT application service users 2) to study data of SAWASDEE by AOT application 3) to study modern marketing strategies of SAWASDEE by AOT application and 4) to study service quality of SAWASDEE by AOT application. Research Methods: Quantitative research with questionnaire instruments, data collection from 420 service users in Suvarnabhumi Airport. Statistics in use were frequency distribution, percentage, mean and standard deviation, t-test and f-test test (one-way ANOVA), and correlation coefficient. Research Results: Mostly personal data were obtained from Generation Z respondents (or the one whose age are under 24 years old). The information from SAWASDEE application found that the opinion level towards flight information accuracy of flight information was at a highest strongly agreed level. Modern marketing strategies (4Es) for worthiness was at a strongly agreed level. Theory/Policy: The authority of Suvarnabhumi Airport should create perception to publicize “SAWASDEE by AOT” to reach the other groups, particularly Baby boomer, which are soon growing population in every country around the globe.